ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERINGKAT OBLIGASI - Ratih Umroh Mahfudhoh; Nur Cahyonowati (Diponegoro Journal of Accounting, 2014)
Bond rating is something that should be considered for investors and issuers before making a decision on bond investment. Bond rating provides an informative statement and signals about the probability of failur of a company’s debt. The purpose of this research is to providing emipical evidance on any factors that possibly affect bond rating prediction. This study examines the role of accounting data and non accounting data in predicting the accurance of bond rating. The accounting data consist of firm size, liquidity, profitability, leverage, productivity, retained earning, and growth. The non accounting data consist of secure and maturity. This research has 74 firms that are listed in PT PEFINDO from 2009 to 2012 except Bank and Financial Institution. Research hypothesis tested by Logistic Regression. The finding of this research: 1) liquidity, profitability, leverage, productivity, growth, secure and maturity are insignificant variable to determine bond rating, and 2) firm size and retained earning are significant variable to determined bond rating.